Biosilica slab photonic crystals as an alternative to cleanroom nanofabrication?. (29th July 2020) - Goessling, Johannes W.; Santiago González, Ana A.; Paul Raj, Vijaya Shanthi; Ashworth, Matt P.; Manning, Schonna R.; Lopez-Garcia, Martin
Abstract : We propose that optical materials produced by diatoms could serve as cost-effective and environmentally friendly alternatives to cleanroom nanofabrication. Abstract : Photonics, the manipulation of light at nanoscale, is a key enabling technology with impact in health and energy applications, among others. In most cases photonics still relies on materials and fabrication methods inherited from other disciplines, usually requiring expensive, time-consuming and environmentally-unfriendly processes. Recent experiments demonstrated that advanced photonic materials, as complex as those known as 2.5 dimensional slab photonic crystals, also occur naturally in diatoms. These microscopic algae precipitate silicic acid from water to produce silicon dioxide membranes, relying on intracellular biomineralization mechanisms. Addressing some important aspects for the potential industrial utilization of these structures, we here propose that optical materials produced by the diatoms could serve as cost-effective and environmentally friendly alternatives to cleanroom nanofabrication. We demonstrate that photonic materials grown by the diatom species Coscinodiscus granii can be separated based on its hydrokinetic characteristics. We further show that the photonic membranes present low defect rates of ca. 1/100 unit cells and that variation in pore diameter, as observed between individual membranes, can affect the photonic properties at large, but only marginally at low refractive index contrast. Finally, we list algal culture collections operating worldwide, thus providing a global network for live diatoms and diatom materials. We discuss the feasibility and bottlenecks related to scaled-up growth for direct utilization of photonic materials from diatoms.